Psoriasis and Cardiovascular Risk-Do Promising New Biomarkers Have Clinical Impact? - Sirje Kaur; Külli Kingo; Mihkel Zilmer (Hindawi Limited, 2017)
Epidemiological studies suggest an increased prevalence of cardiovascular disease (CVD) in patients with psoriasis (PS). Therefore, emphasis has lately been laid on the necessity for clinical evaluation of the risk of CVD in these patients. The systemic inflammatory markers C-reactive protein (CRP) and interleukin- (IL-) 6, which have long been used to predict future CVD in the general population, are increased manyfold in patients with PS. Lipid abnormalities characterized by elevated triglycerides, low HDL cholesterol, and higher concentrations of LDL cholesterol and its oxidized form are also prevalent in patients. There is a need for additional laboratory markers for the assessment of cardiovascular status of patients with PS. Due to frequent comorbid overweight and obesity, biologically active compounds produced by adipocytes may have an impact on monitoring the status of the cardiovascular system of patients with PS. For this purpose, two adipokines, adiponectin and leptin, have been most extensively studied. The review focuses on some inflammatory and oxidative stress aspects in patients with PS through the analysis of the impact of prominent adipokines and oxidized low-density lipoprotein (oxLDL) to assess their eligibility for clinical practice as markers of CVD risk in patients with PS.